Catalytic asymmetric hydrogenation using a [2.2]paracyclophane based chiral 1, 2, 3-triazol-5-ylidene–Pd complex under ambient conditions and 1 atmosphere of H2. Issue 28 (24th February 2015) - Dasgupta, Ayan; Ramkumar, Venkatachalam; Sankararaman, Sethuraman
Abstract : 1, 2, 3-Triazol-5-ylidene–Pd complexes with the planar chiral [2.2]paracyclophane group have been synthesized, structurally characterized and used as catalysts for asymmetric hydrogenation. Abstract : Chiral 1, 2, 3-triazol-5-ylidene–Pd complexes with the planar chiral [2.2]paracyclophane wing tip group have been synthesized and structurally characterized. The complex with a labile acetonitrile co-ligand is an excellent catalyst for chemoselective hydrogenation of alkynes and alkenes and enantioselective hydrogenation of prochiral alkenes at ambient conditions and 1.0 atmosphere of H2 .